Interpersonal relationship - Lituañas, Cyril Ryan A. (Animo Repository, 2000)
A lot of people today especially the young project a virtual kind of life where new gadgets such as hi-tech mobile phones and internet are commonly used. It facilitates life and sometimes helps break routine. It offers comfort and convenience which everybody wishes to get and enjoy. The use of this phenomenon opens up disadvantages too most especially in valuing quality and genuine human and interpersonal relationships. Problems of miscommunication arise to many students due to lack of the basic elements in relationship and communication. Thus, the organizers saw the need to correct the many practices of their fellow students in relating to others and improve interpersonal skills. Hence, the need to present the dynamics in basic communication and listening was important for the 2nd year values education students of Philippine Normal University.